Exploring Ubuntu Philosophy as a Foundation for Holistic School Social Work in South Africa - Boboyi, Asanda (Research in Social Sciences and Technology- OpenED Network, 2024)
This conceptual paper examines the integration of Ubuntu philosophy into school social work practice in South Africa, proposing a transformative framework rooted in interconnectedness, compassion, and community. Drawing from critical social work theories, cultural humility, and restorative justice, the study explores the potential benefits of incorporating Ubuntu in addressing the diverse needs of students. Key findings highlight the positive impact on academic outcomes, community cohesion, and the creation of a more culturally responsive educational environment. The study emphasizes the importance of cultural competence, community engagement, and restorative practices in shaping interventions. Significantly, the study contributes to a growing body of literature on culturally responsive social work practices, providing insights that can inform transformative approaches to school social work in South Africa and potentially beyond.